2022
DOI: 10.3389/fsurg.2022.716510
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Revision Total Knee Arthroplasty Stems at a High-Volume Revision Center

Abstract: IntroductionHybrid fixation and fully cemented fixation are commonly used in revision total knee arthroplasty (rTKA). These two techniques are typically done based on surgeon preference and one has not demonstrated superiority over the other. The purpose of this study was to examine if there was a difference in survivorship between the two different techniques.MethodsA retrospective cohort study of all consecutive patients undergoing rTKA (CPT 27487) from January 1, 2011 to January 1, 2018 at a single academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Follow-up ranged from 2 to 114 months with an average follow-up of 25 months, and the researchers found no significant difference in outcomes between cemented and hybrid stems. 15 Similar results were reported in a meta-analysis by Wang et al that explored outcomes from 17 studies. 7 While some literature exists demonstrating superior anatomic alignment with offset stem use compared with straight stems, there has been no data supporting differences in patient outcomes between fixation methods.…”
supporting
confidence: 80%
“…Follow-up ranged from 2 to 114 months with an average follow-up of 25 months, and the researchers found no significant difference in outcomes between cemented and hybrid stems. 15 Similar results were reported in a meta-analysis by Wang et al that explored outcomes from 17 studies. 7 While some literature exists demonstrating superior anatomic alignment with offset stem use compared with straight stems, there has been no data supporting differences in patient outcomes between fixation methods.…”
supporting
confidence: 80%
“…On the contrary, studies by Gomez et al, Gililland et al and Jacquet et al studied all aseptic causes of primary TKA failure [ 19 21 ]. The rest of the studies included all indications of revision TKAs including loosening, infection, instability, osteolysis or polywear, stiffness, malposition, arthrofibrosis and patellar subluxation [ 16 , 22 25 ]. Majority of the studies included in this systematic review were from the United States of America (USA).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, there were no studies from Asian countries. Majority of the studies reported the implants that they opted for apart from four of the studies that did not specify [ 16 , 20 , 23 , 25 ]. Most studies explicitly detailed their post-operative care for their patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, higher failure rates have been reported in rTKA cases without the use of intramedullary stems, where failure rates increased from 8% with stem usage to as high as 66% without stems at 5-year followup [51,52]. However, the choice of the most appropriate fixation technique remains a challenging decision [32].…”
Section: Discussionmentioning
confidence: 99%